2019
DOI: 10.1002/ams2.390
|View full text |Cite
|
Sign up to set email alerts
|

Advanced cadaver‐based educational seminar for trauma surgery using saturated salt solution‐embalmed cadavers

Abstract: Aim Senior surgeons in Japan who participated in “cadaver‐based educational seminar for trauma surgery (CESTS)” subsequently stated their interest in seminars for more difficult procedures. Therefore, we held a 1‐day advanced‐CESTS with saturated salt solution (SSS)‐embalmed cadavers and assessed its effectiveness for surgical skills training (SST). Methods Data were collected from three seminars carried out from September 2015 to January 2018, including a 10‐point self‐assessment of confidence levels (SACL) q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…We previously reported that basic and advanced C-BEST were useful for trauma surgery training [6,7]. Nonetheless, the issue was that SACL at half a year after the seminar was decreased compared with SACL immediately after the seminar.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We previously reported that basic and advanced C-BEST were useful for trauma surgery training [6,7]. Nonetheless, the issue was that SACL at half a year after the seminar was decreased compared with SACL immediately after the seminar.…”
Section: Discussionmentioning
confidence: 98%
“…We previously reported that cadaver-based educational seminar for trauma surgery (C-BEST) and advanced C-BEST were useful for trauma surgery training. Furthermore, we highlighted the issue that the self-assessment of confidence levels (SACL) at half a year after the seminar decreased compared with SACL immediately after the seminar [6,7]. Regarding this issue, we also speculated that repeated participation in seminars would prevent the decline because other simulation seminars reported that repeated participation could maintain the skills.…”
Section: Introductionmentioning
confidence: 96%
“…Showed great financial advantage by using only water and salt, keeping the texture and color of the cadavers of humans and animals very close to the living ones. However, there are uncertainties about their durability and there is a need for refrigerators or containers for immersion and cadaver maintenance, creating the necessity for lifting equipment (Burns et al, 2018;Hayashi et al, 2014;Homma et al, 2019;Lombardero et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the contexts of health colleges and biological museums, the use of human and animal cadavers occurs as a tool for education as well as to inspire future generations. Despite the modern virtual alternatives in education, the visualization and manipulation of cadavers remain as the gold standard in this matter, considered distinct, and there is still no viable alternative to change, especially in the surgical and clinical training (Burns et al, 2018;Hayashi et al, 2014;Homma et al, 2019;Patel & Moxham, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(table:1) This solution was used in cadavers used for orthopedic surgical training, anatomy dissection and advanced trauma surgical training workshop model [42,43]. An advanced "cadaver based educational seminar for trauma surgery" found SSS method of fixation to be advantageous with reduced level of formaldehyde exposure [44]. Evaluation of comparative fixation efficacy in cadavers among the three common solutions, SSS, Thiel solution and formalin solution for skills training concluded that SSS exhibited a greater level of maintenance of tissue integrity.…”
Section: Saturated Salt Solution (Sss) Embalming Method: -(1998)mentioning
confidence: 99%